Prevalence of cervical ribs and elongated transverse processes in Kashmiri population - Bhat, Mudasir Hamid; Mir, Tariq Abdullah; Abdullah, Ishtiyaq (International Journal of Research in Medical Sciences, 2017)
Background: The aim of this study was to describe the prevalence of cervical ribs and elongated transverse process in the Kashmiri population. Methods: We reviewed 2000 chest x rays of adult patients which were done in a period of 4 months in the department of Radiology, Govt Medical College Hospital, Srinagar, J& K. Results: The diagnosis of cervical rib was made in a total of 50 radiographs with a prevalence of 2.67%. The prevalence of cervical rib was higher in females (3.1%) as compared to males (2.1%). A total of 67 cervical ribs were seen in 50 patients. Unilateral cervical rib was seen in 33(66.0%) patients, right sided in 20(40.0%) and left sided in 13(26.0%). Bilateral cervical ribs were seen in 17(34.0%) patients. Elongated transverse process was seen in 280 patients constituting a prevalence of 14.96%. The prevalence in females (17.95%) was higher than males (12.15%). Conclusions: Prevalence of cervical rib and C7 transversomegaly is high in Kashmiri population. Similar results have been noted in Saudi population. Thus it is concluded that in the populations with higher rates of consanguinity, there is high probability of occurrence of cervical ribs because of HOX gene mutations. There is need for many more well designed studies to prove this association. Keeping in mind the high prevalence of cervical rib, patients with unexplained cervical pain need to be evaluated for this entity.